Quinazolin-derived myeloperoxidase inhibitor suppresses influenza A virus-induced reactive oxygen species, pro-inflammatory mediators and improves cell survival. - Juan A De La Cruz (Public Library of Science (PLoS), 2021)
Superoxide radicals and other reactive oxygen species (ROS) are implicated in influenza A virus-induced inflammation. In this in vitro study, we evaluated the effects of TG6-44, a novel quinazolin-derived myeloperoxidase-specific ROS inhibitor, on influenza A virus (A/X31) infection using THP-1 lung monocytic cells and freshly isolated peripheral blood mononuclear cells (PBMC). TG6-44 significantly decreased A/X31-induced ROS and virus-induced inflammatory mediators in THP-1 cells (IL-6, IFN-γ, MCP-1, TNF-α, MIP-1β) and in human PBMC (IL-6, IL-8, TNF-α, MCP-1). Interestingly, TG6-44-treated THP-1 cells showed a decrease in percent cells expressing viral nucleoprotein, as well as a delay in translocation of viral nucleoprotein into the nucleus. Furthermore, in influenza A virus-infected cells, TG6-44 treatment led to suppression of virus-induced cell death as evidenced by decreased caspase-3 activation, decreased proportion of Annexin V+PI+ cells, and increased Bcl-2 phosphorylation. Taken together, our results demonstrate the anti-inflammatory and anti-infective effects of TG6-44.